Penggunaan Media Puzzle Untuk Meningkatkan Kreatifitas Kelompok Siswa Pada Pembelajaran Bahasa Indonesia di Sekolah Dasar - Annisa Khairani, Ilmi; Octavia , Nisagita; Prihantini , Prihantini (Jurnal Multidisiplin Indonesia, 2023)
The use of learning aids has a crucial role in achieving learning objectives. The learning process occurs through the interaction of individuals with their environment. Indicators of learning success lie in behavioral changes in knowledge, skills, or attitudes that arise as a result of experiences and practices experienced by individuals (Yunita & Supriatna, 2021). This study investigates the use of puzzle media in enhancing students' creativity in Indonesian language learning at primary school. The research involves an experimental method with a focus on student group creativity. The use of puzzle media as a learning tool is believed to stimulate students' creative thinking in the context of language learning. Data were collected through observation, creativity tests, and analysis of group work results. The results of this study provide significant evidence of the effectiveness of puzzle media in improving students' creativity in Indonesian language learning in elementary schools.